2005
DOI: 10.1136/bjsm.2004.017566
|View full text |Cite
|
Sign up to set email alerts
|

Release of α-actin into serum after skeletal muscle damage

Abstract: Objective: The skeletal muscle protein α-actin was investigated in the serum of subjects with severe skeletal muscle damage to assess its utility as a reliable and predictive marker of muscle damage.Methods: Serum samples were obtained from 33 healthy controls and 33 patients with severe skeletal muscle damage, defined by a total creatine kinase value of >500 IU/l (Rosalki method). Troponin I, troponin T, and myoglobin concentrations were determined by immunoassay and α-actin concentrations by Western blot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 32 publications
0
33
0
2
Order By: Relevance
“…Lazarim et al 10 , reported that in his study, one soccer player whose CK concentration exceeded the proposed reference value was injured. During the present study, four soccer players underwent muscle injury, with two of them presenting CK Game above their CK Max, This may suggest the occurrence of a higher rupture of the muscle tissues, resulting in a larger extravasation of CK into the blood stream 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Lazarim et al 10 , reported that in his study, one soccer player whose CK concentration exceeded the proposed reference value was injured. During the present study, four soccer players underwent muscle injury, with two of them presenting CK Game above their CK Max, This may suggest the occurrence of a higher rupture of the muscle tissues, resulting in a larger extravasation of CK into the blood stream 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Microtrauma and damage can be determined by measuring IL-6 6,10 , CK 13 and alpha-actin 11,12 , all of which are present in the blood and result from muscle rupture.…”
Section: Discussionmentioning
confidence: 99%
“…Activities with high intensity and high demand on the musculoskeletal system, such as soccer, result in high levels of muscle microtrauma 6,10 . Microtrauma can be evaluated by measuring the blood levels of muscle alpha-actin 11,12 and creatine kinase (CK) 13 , which come from the sarcoplasm. Monitoring acute response to exercise, especially in specific, real-life situations such as competitive soccer matches, provides important information for further understanding the demand imposed on the body.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of CK, these include mitochondrial CPK, CPK-immunoglobulin complexes and CPK derived from cardiac muscle (Martinez-Amat et al, 2005). In addition, total levels have also been found to depend on age, gender, ethnicity, muscle mass, climatic condition and exercise mode and intensity (Brancaccio et al, 2007;Mckune et al, 2012), all of which can affect enzyme tissue activity and subsequent serum levels (Baird et al, 2012).…”
Section: Creatine Phosphokinase (Cpk) and Lactate Dehydrogenase (Ldh)mentioning
confidence: 99%